Dentin microhardness and porosity of wistar rats teeth following herbal-based devitalizing agent application - Maria Tanumiharja; Mustakim Mustakim; Aries C. Trilaksana; Lukman Muslimin (DiscoverSys Inc., 2022)
Objective: To evaluate the microhardness and porosity of the dentin of Wistar rats after pulp-out application. Materials and Methods: This was laboratory experimental research with posttest design with control group. Twelve teeth of wistar rats were allocated into 2 groups, the test group and the control group. In the test group, teeth were prepared on the labial surface until half thickness of the dentin, then pulpout was applied to the base of cavity, covered with GIC. On the 7th day, euthanasia and extraction were performed to test the dentin microhardness with Vickers Hardness Tester and dentin porosity with Laser Scanning Microscope (LSM). Results: The mean value of tooth hardness after pulp-out application was 22.23 ± 3.51 HV while the mean value of the control group was 27.70 ± 1.70 HV, with p value = 0.31 at 95% significance level. There was a decrease in tooth hardness of treated sample which was not significantly different compared to the control group. CLSM photo shows white lines on the sample surface as the exposed dentinal tubules with a higher intensity compared to the control group. Conclusion: Pulp-out decreased tooth microhardness and cause porosity of the teeth.